Effects of rearing and adult laying housing systems on medullary, pneumatic and radius bone attributes in 73-wk old Lohmann LSL lite hens. (27th March 2019) - Neijat, M; Casey-Trott, T M; Robinson, S; Widowski, T M; Kiarie, E
ABSTRACT: We determine interactive effect of a combined model of housing systems for rearing pullets and raising adult birds on bone quality. The LSL-Lite pullets were reared in either an aviary system (A ) or conventional cages (C ). At week 16, the birds were transferred either to the same housing type through the adult stage (A-A or C-C, for rearing and adult phase, respectively) or to enriched system (A-E or C-E, respectively). In the rearing stage, C cages housed 16 pullets/cage (week 0 to 6) and 8 pullets/cage (week 6 to 16) with a space allowance of 145 and 290 cm 2 /pullet, respectively; the rearing aviary housed 756 pullets/enclosure allowing 285 cm 2 /pullet (week 0 to 6) and 754 cm 2 /pullet (week 6 to 16). In the adult phase, C cages were 58.4 cm wide × 66.0 cm deep (482 cm 2 /pullet, 8 pullets/cage). For adult A, a commercial multi-tier aviary provided a space allowance >1000 cm 2 /hen system with litter area. Enriched system housed 60 birds/cage at 750 cm 2 /bird with perches, nest, and scratch mat. Bone samples were collected from the adult phase (week 73) and analysed for bone quality indices including bone breaking strength (BBS ), total bone weight (TBW ), ash content of the medullary (femur and tibia), pneumatic (humerus and keel), and radius bones. The A-A hens had the greatest ( P < 0.05) TBW for medullary (femur and tibia) and pneumatic (humerus and keel) bones compared with hens from other housing models with exception of C-E hens. In addition, ash content was heavier ( P = 0.048) for both A-A and C-E managed birds compared to the other housing. Birds in C-C system had the least score ( P < 0.05) for TBW and ash content in all bone types. Regardless of the housing system, BBS was correlated (r = 0.60; P < 0.01) with the amount of ash and TBW, particularly for humerus and tibia. The results provide an insight on the impact of type of housing system in rearing and production stages on late cycle bone quality.